Call Options, Points, and Dominance Restrictions on Debt Contracts - Dunn, Kenneth B.; Spatt, Chester S. (Journal of Finance, 1999)
We analyze the impact of a contract's length, callability, amortization, and original discount by arbitrage methods. Among instruments that are callable without penalty, longer instruments command a higher interest rate because the borrower possesses the option of repaying relatively more slowly. However, the rate on longer self‐amortizing loans cannot be substantially larger than for shorter ones because the payments decrease with contract length. Bounds on the trade‐off between points and rate for callable debt are characterized using the trade‐off for noncallable debt and the property that the value of the prepayment option increases with the loan's interest rate.